Protein-to-energy ratio of 21.43 g MJ−1 improves growth performance of Nile tilapia at the final rearing stage under commercially intensive rearing conditions - Koch, J. F.A. [UNESP]; Barros, M. M. [UNESP]; Teixeira, C. P. [UNESP]; Carvalho, P. L.P.F. [UNESP]; Fernandes Junior, A. C. [UNESP]; Cintra, F. T. [UNESP]; Pezzato, L. E. [UNESP] (Wiley, 2017)
This study evaluated the effect of ratio of dietary digestible protein (DP) to digestible energy (DE) on growth performance, fillet chemical composition and haematological profile of Nile tilapia subjected to transport-induced stress at the final rearing stage (450 to 800 g) under commercial conditions. The trial was conducted using a 5 × 2 factorial layout (DP: 200, 230, 260, 290 and 320 g kg−1) and (DE: 12.6 and 13.8 MJ kg−1). Energy levels did not influence any analysed parameters in this research. Final weight and biomass gain were increased up to the ratio of 269 and 270 g PD kg−1, respectively, and feed conversion ratio was reduced down to a 275 g DP kg−1. Protein efficiency ratio linearly decreased from 200 g DP kg−1 diet to 320 g DP kg−1. There was no statistical difference in fillet chemical composition. Red blood cell count (RBC), haemoglobin (Hb), mean corpuscular volume (MCV) and mean corpuscular haemoglobin concentration (MCHC) were different before and after transport-induced stress. Leucocyte differentiation after transport-induced stress revealed lymphocytopenia and neutrophilia. We conclude that for tilapia weighing 450–800 g reared under commercially intensive conditions, a diet with 270 g DP kg−1 and 12.6 MJ DE kg−1 (21.43 g DP MJ−1 DE) can improve the growth performance and ensure the fish health.
Keywords: fillet yield; floating net cages; growth performance; hematological profile; transport-induced stress